Hsa-miR-27b is up-regulated in cytomegalovirus-infected human glioma cells, targets engrailed-2 and inhibits its expression. Issue 12 (June 2017) - Wang, Linqian; Yang, Ming; Liao, Shijing; Liu, Wei; Dai, Gan; Wu, Guojun; Chen, Liyu
Human cytomegalovirus (HCMV) dormant infection can alter the expression of the hosts' microRNAs (miRNAs) and impact on the regulation of target genes. To investigate the differentially expressed miRNAs induced by HCMV in human glioma U251 cells, a comprehensive miRNA screen was performed. As a result, 19 up-regulated and 14 down-regulated miRNAs were determined. Of these, hsa-miR-27b (miR-27b) attracted our attention. MiR-27b levels in U251 cells increased 7.70-fold, 8.64-fold, and 4.78-fold, respectively, post 24 h, 48 h, and 72 h HCMV infection, compared to those in the mimic-infected cells, and this up-regulation was further confirmed by quantitative RT-PCR. The bioinformatic analyses show that miR-27b targets engrailed-2 (EN2) gene; however, the effect of miR-27b on EN2 is rarely encountered. In this study, we initially conducted dual luciferase assay to validate the target function of miR-27b on EN2. The results manifested that EN2 is a novel target of miR-27b, which could directly target the 3′ untranslated region (3′-UTR) of the gene. We further found that the miR-27b transfected glioma U251 cells exhibited longer cell bodies with more synapses and multiple-angle shapes; moreover, Western blot detection revealed that the EN2 protein levels in these cells were significantly low. In conclusion, our study originally reports the up-regulation of miR-27b in HCMV-infected glioma cells. Our study also provides the first experimental evidence that miR-27b could affect glioma cells' growth, target EN2 and inhibit its expression in glioma cells. Our data indicate that miR-27b may be related to the development of neurological disorders with HCMV infection. The newly identified miR-27b/EN2 signal pathway may provide new insights into the glioma pathogenesis and a novel target for glioma therapy. Impact statement: Our study is the first to demonstrate that the HCMV infection could alter the expression of cellular microRNAs of the host glioma cells, which may develop an understanding of the pathogenesis of the HCMV infection in the microRNA level. Recently, HCMV infection and engrailed-2 have been reported to be related to the autism spectrum disorder (ASD). In this study, we confirmed that engrailed-2 is the target of hsa-miR-27b. As far as we know, our findings of the hsa-miR-27b up-regulation in the HCMV-infected glioma cells, targeting engrailed-2 and inhibiting its expression have never been reported or documented. Our data indicate that miR-27b may be related to the development of neurological disorders with the HCMV infection. The newly identified miR-27b/EN2 signal pathway may provide new insights into the glioma pathogenesis and a novel target for glioma therapy.